Statistical parametric mapping for the analysis of pacing strategies in skiing sports - Staunton, C. A. (Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden, 2022)
Aim This presentation aimed to summarise the findings from a series of studies in skiing sports (XC skiing and biathlon) that have used Statistical Parametric Mapping (SPM) for the analyses of micro-pacing strategies. SPM is a novel statistical technique which has been promoted for analysis of smooth biomechanical data like speed collected from position system technoliges.1,2